Sistem Pengecekan Grammar Abstrak Laporan Tugas Akhir dan Magang pada Mahasiswa Teknik Universitas Gajah Putih Menggunakan Metode Stemming - Ira Zulfa; Eliyin Eliyin; Isna Ayuning Tias (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to develop a grammar checking system on abstracts of internship and thesis reports at the Faculty of Engineering, Gajah Putih University Takengon (UGP). This system is designed to detect errors in the use of words and tenses by utilizing the stemming method in the language analysis process. The application development approach uses the PHP programming language and the Code Igniter framework to optimize system performance. The research stages include needs analysis, system design, program code implementation, and application testing. The test results showed that the stemming method was able to effectively identify Tenses errors in the abstract of the internship report and thesis. This finding is expected to help students in compiling abstracts that are in accordance with academic English rules and support lecturers in the process of evaluating scientific papers. In addition, this system contributes to improving the quality of academic writing within the Faculty of Engineering UGP by providing practical, efficient, and integrated tools. Thus, the development of a grammar checking system based on PHP and Code Igniter can be an innovative solution in supporting the improvement of students' academic quality and language skills.